Law Enforcement of The Criminal Action of Spreading Pornography Videos Through Social Media (Decision Study Number 2661/Pid.Sus/2020/Pn. Mdn) - Ali Bahardin, (Mahadi: Indonesia Journal of Law, 2023)
Pornography has such a negative impact on human life that there needs to be a concerted effort against pornography across society so that it does not lead to a denial of what it means to be human. In preparing this paper, secondary sources were examined using library search methods by analyzing Case No. 2661/Pid.Sus/2020/PN. The conclusion of the oral debate was that the legal regulation against the offense of distributing pornographic videos uploaded via social media was incorporated into the Criminal Code, then Law No. 11 of 2008 on Information and Electronic Transactions and Law No. 44 of 2008. is to be incorporated into Pornography is regulated. The implementation of prosecution for the offense of distributing pornographic videos uploaded via social media is based on the provisions of the Criminal Code, Article 27(1) of the Information and Electronic Transactions Law No. 19 of 2016. Distribution of pornographic videos uploaded via social media under Decision No. 2661/Pid.Sus/2020/PN. Mdn meets all elements of Section 29 of RI Act No. 44 of 2008 regarding Pornography.